Maternity care experiences and outcomes of people seeking sanctuary in Wales: a data linkage study protocol - Bukkfalvi-Cadotte, Alix; Khanom, Ashra; Brown, Amy; Snooks, Helen (International Journal of Population Data Science, 2024)
Introduction People seeking sanctuary, including refugees and asylum seekers, face barriers and challenges in accessing high quality healthcare. In maternity care specifically, asylum-seeking and refugee women are less likely to access timely and adequate antenatal care and may be more likely to experience adverse perinatal outcomes. Objectives We aim to describe maternity care service users seeking sanctuary in Wales and determine whether their perinatal health outcomes and use of maternity care services differ from women born in the UK. Methods We will conduct a retrospective cohort study. Linking six datasets held by SAIL Databank, we will identify individuals recorded as refugees or asylum seekers in General Practitioner (GP) records. We will conduct a descriptive analysis of their demographic and health characteristics and conduct a comparative analysis of maternity care service use and perinatal health outcomes between refugees and asylum seekers and UK-born individuals. We will identify statistically significant differences between groups, and where the completeness and quality of the data allow, we will adjust for known covariates. Results This study will enable us to report on the characteristics of maternity care service users seeking sanctuary in Wales, their maternity care service use and perinatal health outcomes compared to UK-born women. Conclusions This data linkage study will enhance our understanding of health inequities in maternity care and perinatal outcomes related to asylum seeker or refugee status. Results will inform policy and practice to improve provision of maternity care to women seeking sanctuary.